Pituitary Metastasis of Lung Neuroendocrine Carcinoma Mimicking Pituitary Adenoma:Case Report and Literature Review - Liu, Xiaohai; Wang, Renzhi; Li, Mingchu; Chen, Ge (Frontiers in Endocrinology, 2021)
Pituitary metastasis is an unusual situation in clinical practice, with increasing morbidity as the population ages. The most common primary cancer sites are the breast in women and the lung in men. However, diagnosing asymptomatic patients with unknown malignant neoplasms may be very difficult, and pituitary metastasis may be diagnosed as pituitary adenoma. Here, we describe a case of a 65-year-old patient with clinical visual changes and diabetes insipidus who showed an extensive mass in the sellar region initially thought to be a pituitary adenoma. The corticotropic deficits were corrected, transnasal transsphenoidal surgery was adopted, and the tumor was totally resected. The tumor texture during surgery was similar to that of pituitary adenoma, but the histopathological and immunohistochemistry analyses revealed pituitary metastasis of a lung neuroendocrine tumor. Postoperatively, a chest CT scan confirmed a pulmonary mass consistent with the primary neoplasm. Abdominal CT revealed multiple metastases in the liver, pancreas and colon. Despite intensive treatment, the patient continued to show a decreased level of consciousness due to dyscrasia, leading to death 1 week after surgery. Our case highlights the importance of a differential diagnosis of invasive lesions of the sellar region, mainly in individuals over 60 years of age, especially those with diabetes insipidus.